Clinical associations of Dupuytren's disease. Issue 957 (5th July 2005) - Hart, M G; Hooper, G
Abstract : Dupuytren's disease (DD) is a common progressive fibrotic condition affecting the palmar and digital fascia. Although its management is undertaken by hand surgeons, it is commonly seen by other doctors as an incidental finding. In many cases it is believed to be associated with other medical conditions, although the evidence for such associations is not always clear. This review considers the evidence behind these associations and discusses the aetiology of DD. By doing so, it is hoped that this review will permit a better understanding of the relevance of DD as a clinical sign.